Traditional Balinese Food Existence and Appealing as The Culinary Tourism at Stars Hotels at Sanur Denpasar Bali - Eka Putri, Ida Ayu Trisna; Kesumadewi, Putu Dian (Journal of A Sustainable Global South; Vol 1 No 1 (2017): February 2017DO - 10.24843/jsgs.2017.v01.i01.p02, 2020)
The purpose  of this  study is determining  the  existence,  appealing,  and also the tourist  perception  of Traditional Balinese  Food  at stars hotels  in  Sanur.  The  research  sample  is  whole  the  four  and  five  star hotels  in  Sanur.  The  purposive technique  as used in determining the research informant by interviewed with the hotel chef. The tourist perception  was collected by   accidental   sampling.   Data   collected   by   observation,   interviewed,   literature   study,   questionnaires,    and   the   picture documentation.  The data were analyzed by descriptive method and Likert Scale for the tourist perception. According to this research that most of the stars hotels at Sanur presents, and served with various menus, and the favorites menu is  "  Ikan  Panggang  Sambel  Matah".  The  cooking  process, with  decreased  the  high  spicy  and  add  the  sweet  taste  is  the modification  of the food for serving to the foreign tourist.  The presentation  by buffet and a la carte service.   The Likert scale measurement  shows that the presentation  quality gets the highest score, total score is 382 (mean 4,24), and the lowest score is the variety of the menu with a total score 353  (mean 3,92). Keywords:   existence, appealing, Traditional Balinese Food, the stars hotels